2011
DOI: 10.1152/ajpregu.00525.2010
|View full text |Cite
|
Sign up to set email alerts
|

High doses of vitamin E improve mitochondrial dysfunction in rat hippocampus and frontal cortex upon aging

Abstract: Rat aging from 4 to 12 mo was accompanied by hippocampus and frontal cortex mitochondrial dysfunction, with decreases of 23 to 53% in tissue and mitochondrial respiration and in the activities of complexes I and IV and of mitochondrial nitric oxide synthase (mtNOS) (P < 0.02). In aged rats, the two brain areas showed mitochondria with higher content (35-78%) of oxidation products of phospholipids and proteins and with higher (59-95%) rates of O(2)(-) and H(2)O(2) production (P < 0.02). Dietary supplementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…Additionally, mRNA expression of respiratory system complexes I and IV as well as protein expression of complexes I, IV and V was numerically or significantly decreased which might contribute to impaired mitochondrial respiration in the brains of aged NMRI mice. Our findings about impaired brain mitochondrial function in aged mice very well match existing literature data about brain mitochondrial dysfunction in aged mice (Afshordel et al 2015;Navarro et al 2002Navarro et al , 2005Navarro et al , 2011 as recently discussed in detail (Hagl et al 2016). We additionally found that mRNA and protein expression of proteins associated with fission and fusion processes were changed in aged NMRI mice.…”
Section: Mitochondrial Dysfunction In Aged Micesupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, mRNA expression of respiratory system complexes I and IV as well as protein expression of complexes I, IV and V was numerically or significantly decreased which might contribute to impaired mitochondrial respiration in the brains of aged NMRI mice. Our findings about impaired brain mitochondrial function in aged mice very well match existing literature data about brain mitochondrial dysfunction in aged mice (Afshordel et al 2015;Navarro et al 2002Navarro et al , 2005Navarro et al , 2011 as recently discussed in detail (Hagl et al 2016). We additionally found that mRNA and protein expression of proteins associated with fission and fusion processes were changed in aged NMRI mice.…”
Section: Mitochondrial Dysfunction In Aged Micesupporting
confidence: 91%
“…Similarly, RBE administration to young guinea pigs ameliorated brain mitochondrial function by increasing mitochondrial content and by protecting cells from nitrosative stress (Hagl et al 2013). Navarro and coworkers reported that a-tocopherol, which is a key component of RBE, increased brain mitochondrial function (respiration, ATP production, mitochondrial content) in aging rats (Navarro et al 2011) and mice (Navarro et al 2005).…”
Section: Rice Bran Extract Ameliorates Mitochondrial Dysfunction In Amentioning
confidence: 99%
“…Although not free of discrepancy (236), multiple studies have shown the occurrence of a mitochondrial nitric oxide synthase (mtNOS) in several tissues [including brain (233) and with a function in rat brain development (200)] by its biochemical activity and by the inhibition of mitochondrial respiration elicited by NOS substrates and inhibitors (167,171,172). Mitochondrial metabolic states regulate the diffusion of both$NO and H 2 O 2 from mitochondria to cytosol (32,200).…”
mentioning
confidence: 99%
“…44,66,73 In this regard, vitamin E deficiency has been associated with cognitive and motor impairments 43 67,75 and reducing the degeneration of hippocampal cells. 76 Moreover, the antioxidant efficiency of vitamin E is increased after long-term treatments with α-tocopherol because brain tend to increase its concentration (within the lipid bilayer of membranes) 26 in a doseresponse manner, as observed in this work and reported previously.…”
mentioning
confidence: 99%